2015
DOI: 10.28986/jtaken.v1i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Karakteristik Keuangan Dan Hasil Pemeriksaan Pada Kesejahteraan Masyarakat Di Provinsi Sumatera Utara

Abstract: One of the implications of desentralization is a performance measurement of local government. Local government peformance can be seen from the Evaluation of Local Government Performance score (Mustikarini & Fitriasari, 2012), efficiency ratio (Marfiana & Kurniasih, 2013) and the Human Development Index (Prasetyaningsih, 2015). HDI is also an indicator for public welfare, so it can be concluded that local government performance can be measured from the level of its public welfare. This research aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
1
15
1
5
Order By: Relevance
“…Berdasarkan penelitian yang dilakukan oleh Andirfa et al (2016), Alvini et al (2018), Leki et al (2018) dan Mangkunegara (2015) menyatakan bahwa belanja modal berpengaruh positif terhadap kinerja pemerintah daerah. Hal ini menandakan bahwa semakin besar belanja modal maka kinerja penyelenggaraan pemerintah daerah juga akan semakin meningkat.…”
Section: Gambar 1 Ekppd Terhadap Lppd Provinsi DI Indonesia Tahun 20unclassified
See 1 more Smart Citation
“…Berdasarkan penelitian yang dilakukan oleh Andirfa et al (2016), Alvini et al (2018), Leki et al (2018) dan Mangkunegara (2015) menyatakan bahwa belanja modal berpengaruh positif terhadap kinerja pemerintah daerah. Hal ini menandakan bahwa semakin besar belanja modal maka kinerja penyelenggaraan pemerintah daerah juga akan semakin meningkat.…”
Section: Gambar 1 Ekppd Terhadap Lppd Provinsi DI Indonesia Tahun 20unclassified
“…Hal ini nantinya akan berimplikasi terhadap meningkatnya kinerja penyelenggaraan pemerintah daerah. Penelitian ini sejalan dengan penelitian yang dilakukan oleh Andirfa et al (2016), Leki et al (2018) dan Mangkunegara (2015) yang menyatakan bahwa belanja modal berpengaruh positif dan signifikan terhadap kinerja pemerintah daerah.…”
Section: Tabel 2 Hasil Pengujian Asumsi Klasikunclassified
“…The use of government-owned resources will affect the welfare of the community in these 3 (three) basic dimensions. Therefore, Mangkunegara (2015) and Prasetyaningsih (2014) adopted the HDI as a proxy of the financial performance of regional government. Further, Sarjono (2016), Suryaningsih, Utama, & Yasa (2015) and Azwar & Subekan (2014) also discovered that regional financial performance had a significant positive effect on people's welfare.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the government needs the assets of a community health center (community health center) to serve people who needhealth services. Artha, Basuki, & Alamsyah (2015), Mangkunegara (2015), Prasetyaningsih (2014) and Mustikarini & Fitriasari (2012) found that regional assets affect local government performance in improving community welfare. Therefore, assets should be able to influence the financial performance of local governments in improving people's welfare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation